Strategi Guru Pendidikan Agama Islam Dalam Meningkatkan Budaya Religius Siswa Di SMP PGRI Patrol Kabupaten Indramayu - Nurosid, Nurosid; Na’imah, Farida Ulvi; Kholis, Mohammad Maulana Nur (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2024)
This research aims to explore and analyze the strategies of Islamic Religious Education (PAI) teachers in improving students' religious culture at PGRI Patrol Middle School, Indramayu Regency. The research method used is a qualitative approach with a case study type of research. Data collection was carried out through interviews, observation and documentation. The research results show that the process of implementing student religious culture at PGRI Patrol Middle School involves the role and synergy of various parties, such as the school principal, PAI teachers, and all components of the school community. The strategies used by PAI teachers include making rules in the form of policies, getting used to carrying out religious activities, as well as efforts to renew students' mindsets. Obstacles include motivation and commitment from students and teachers, as well as limited facilities and infrastructure. To overcome these obstacles, schools implement policies in the form of punishments and rewards. The implications of this strategy are realized in the creation of attitudes and behavior that reflect Islamic values ??in students, the creation of a comfortable and religious school atmosphere and environment, as well as increased awareness of all school members. The findings of this research strengthen theories and previous research results that are relevant regarding the development of religious culture in schools.